Pengaruh Edukasi Pengawas Minum Obat (PMO) Anti Hipertensi Terhadap Kepatuhan Minum Obat Hipertensi Pada Pasien Di Posbindu Kelurahan Galang Kota - Teguh Karya Darma Tarigan; Harsudianto Silaen (Program Studi Pendidikan Biologi, 2025)
Background: Hypertension is a condition in which blood vessels with diastolic blood pressure are ≥90 mmHg and systolic blood pressure ≥140 mmHg. Medication Supervisors for hypertension are one of the main ways to prevent this hypertension from developing into increasingly severe complications. Objective: To analyze the effect of education on anti-hypertension medication supervisors (PMO) on compliance with taking hypertension medication in patients at the Galang City Post Bindu in 2024. Method: This type of research is a quantitative research type using a quasi-experimental research design with a research design of one group pre-test and one group post-test design. The sampling technique used total sampling with a total of 53 respondents. Data analysis used the Wilcoxon sign rank test. Results: The results of this study indicate that there is a significant influence of education of drug supervisors on compliance with taking hypertension medication with a p-value of 0.000 0.05 and a p-value of 0.002 0.05. Conclusion: There is a significant influence between education of drug supervisors (PMO) for antihypertension on compliance with taking hypertension medication in patients at the Posbindu, Galang City. It is recommended that further research be carried out by adding other variables such as education of hypertension families, eating patterns that can affect hypertension conditions